2022
DOI: 10.3390/v14020446
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Impact of Coinfection in Patients with Coronavirus Disease 2019 in Korea

Abstract: Coinfection rates with other pathogens in coronavirus disease 2019 (COVID-19) varied during the pandemic. We assessed the latest prevalence of coinfection with viruses, bacteria, and fungi in COVID-19 patients for more than one year and its impact on mortality. A total of 436 samples were collected between August 2020 and October 2021. Multiplex real-time PCR, culture, and antimicrobial susceptibility testing were performed to detect pathogens. The coinfection rate of respiratory viruses in COVID-19 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…In the previous studies, the rate of bacterial co-infection in COVID-19 patients varied from 2.7–52.6%. 10 11 12 13 14 15 16 One meta-analysis study published in 2020 found bacterial coinfection in 4.9% of COVID-19 patients on hospital admission and 16.0% on ICU admission. 21 In another meta-analysis study, 7% of hospitalized COVID-19 patients had bacterial co-infection, a number that increased to 14% in studies that only included ICU patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, the rate of bacterial co-infection in COVID-19 patients varied from 2.7–52.6%. 10 11 12 13 14 15 16 One meta-analysis study published in 2020 found bacterial coinfection in 4.9% of COVID-19 patients on hospital admission and 16.0% on ICU admission. 21 In another meta-analysis study, 7% of hospitalized COVID-19 patients had bacterial co-infection, a number that increased to 14% in studies that only included ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, the rates of bacterial co-infection in COVID-19 patients varied from 2.7–52.6% according to hospital settings and regional differences. 10 11 12 13 14 15 16 Second, microbiological testing for bacterial co-infection was conducted in less than half of the study population in most of the studies, which can lead to a substantial bias. 10 13 17 18 19 The purpose of this study was to answer two clinical questions for hospitalized COVID-19 patients: 1) the frequency of bacterial co-infection and 2) the clinical effect of empirical antimicrobial therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings contradict the opinion of some researchers who speculate that seasonal respiratory viruses (e.g., RV) have a shorter incubation period than SARS CoV-2 and induce the production of interferon, which inhibits SARS CoV-2 replication (38). Jeong et al (24) reported that the median cycle threshold value of SARS-CoV-2 testing was slightly elevated in patients with coinfection. In another study, the differences in the mean Ct values between specimens with and without coinfection were not statistically significant (39).…”
Section: Discussionmentioning
confidence: 99%
“…Candida albicans is a human commensal fungus and the etiologic agent of infections in skin, oral and esophageal cavities, gastrointestinal tract, lungs, and bloodstream in immunocompromised individuals ( Kadosh and Lopez-Ribot, 2013 ; Lemberg et al, 2022 ). Although it is considered an opportunistic fungus, C. albicans is the most common cause of nosocomial fungal infections, with a mortality rate of ∼40% in patients with systemic infections ( Gudlaugsson et al, 2003 ; Perlroth et al, 2007 ; Erami et al, 2022 ; Jeong et al, 2022 ). Due to its severity, nosocomial candidemia contributes to prolonged hospitalization, increased healthcare costs, and increased morbidity and mortality rates ( Perlroth et al, 2007 ; Arendrup, 2010 ; Kullberg and Arendrup, 2015 ; Erami et al, 2022 ; Jeong et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is considered an opportunistic fungus, C. albicans is the most common cause of nosocomial fungal infections, with a mortality rate of ∼40% in patients with systemic infections (Gudlaugsson et al, 2003;Perlroth et al, 2007;Erami et al, 2022;Jeong et al, 2022). Due to its severity, nosocomial candidemia contributes to prolonged hospitalization, increased healthcare costs, and increased morbidity and mortality rates (Perlroth et al, 2007;Arendrup, 2010;Kullberg and Arendrup, 2015;Erami et al, 2022;Jeong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%